PERENCANAAN DAN STRATEGI KOMUNIKASI KEMENTERIAN KEUANGAN REPUBLIK INDONESIA TERKAIT ISU CUKAI PLASTIK - nirwana, testa pradia; Ernawati, Erna; Muslikhah, Febri Palupi; ayu, Descia sevilla (JURNAL SAHID DA'WATII, 2024)
The purpose of this study is to analyze the planning model and communication strategy carried out by the Bureau of Communications and Information Services in dealing with issues related to plastic excise. This research method uses a qualitative approach with data collection techniques through observation, interviews, and literature study. The results of this study can be illustrated that the planning and communication strategy of the Bureau related to excise issues through several stages, such as the fact finding stage, the preparation of communication strategies, and the communication stage in the form of delivering information through mass media. The planning stage and communication strategy carried out by BKLI refers to the public relations-based communication planning model by Cultip and the Center.